Self-Protection against UV Exposure: Behavioral Patterns and Phototype Correlations among Medical Students in North Jakarta, Indonesia - Alvina, Jesslyn; Arieselia, Zita; Regina, Regina (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2025)
Introduction: Exposure to ultraviolet (UV) rays can cause significant skin damage, including cancer. This study examines sun protection behaviors among medical students in North Jakarta, despite their knowledge of UV risks, and correlates these behaviors with Fitzpatrick skin types. Understanding these behaviors helps inform targeted interventions to promote sun safety among future healthcare professionals. Methods: An observational study with a cross-sectional approached on 230 respondents consisting of medical students, conducted through online questionnaires within 3-month period on a systematic random sampling method. Data on demographic data, Fitzpatrick skin type scale, and 5 questions on self-protection behavior obtained was analyzed using Spearman’s rank correlation and chi-square analysis, p < 0.05 indicating a significant relationship. Results: Type III, IV, and V are the most common Fitzpatrick’s phototypes found on subjects where 69.6% of students had low sun protection behavior. Male exhibit lower sun protection behavior than female, and there was no relationship between students’ Fitzpatrick's skin type and sun protection behavior, (p = 0.112). Conclusions: Sun protection behavior among medical students at FKIK UAJ is low. There is a correlation between gender and sun protection behavior, but no correlation between Fitzpatrick's skin type and sun protection behavior among the students. The study reveals that medical students, especially males, exhibit low sun protection behaviors despite their knowledge of UV risks, emphasizing the need for targeted educational interventions. These findings are crucial for medical education and public health, making them relevant for journals focused on preventive medicine, dermatology, and medical education.